Next-generation sequencing study on poorly differentiated carcinoma derived from a thirty-year-old epidermoid cyst: A case report - Choi, Woosuk; Park, Joseph Kyu-hyung; Song, Seung Geun; Kim, Baek-kyu (Frontiers in Oncology, 2023)
Although epidermoid cysts are frequently seen as benign lesions, they are highly uncommon to develop into cancerous lesions. A 36-year-old man with a cystic mass present on his left flank since childhood presented to our department. Based on the patient's medical history and abdominal computed tomography scan, we excised the lesion under the suspicion of an epidermoid cyst. Histopathological evaluation revealed the presence of poorly differentiated carcinoma with squamoid and basaloid differentiation, which showed a strong possibility of carcinoma arising from an epidermal cyst. Next-generation sequencing using TruSight oncology 500 assay showed copy number variation of ATM and CHEK1 genes.